Analisis Kesenjangan Budaya Kerja Terhadap Strategi Perubahan Kinerja Karyawan Perkebunan Swasta Mikro di Kabupaten Karanganyar - Utami, Rosita Tri; Suswadi, Suswadi; Irawan, Norbertus Citra (Musamus University, 2025)
Dissatisfaction with the work culture in the workplace can lead to decreased employee motivation, especially if they feel unappreciated, lack opportunities for development, or do not receive adequate incentives. This study aims to understand how gaps in work culture affect employee performance and formulate strategies for better performance improvement. Using a mixed approach that combines quantitative and qualitative methods and descriptive analysis, this study applies a purposive approach to determining the location and a census method for selecting respondents. We analyzed the data using gap analysis and descriptive statistics. The results revealed positive gaps in seven attributes: compliance with regulations, commitment, self-development, appreciation, effective communication, work-life balance, and discipline, all of which require maintenance and improvement. In contrast, teamwork, creativity, and a sense of responsibility show negative gaps, requiring change strategies to improve employee performance transformation effectively.